Kemampuan Guru MAN dalam Pembuatan Media Pembelajaran dengan Video Berbasis Aplikasi Ms Powerpoint pada mata pelajaran Ekonomi: Kemampuan Guru MAN dalam Pembuatan Media Pembelajaran dengan Video Berbasis Aplikasi Ms Powerpoint pada mata pelajaran Ekonomi - Movitaria, Mega Adyna (Institut Agama Islam Sumatera Barat Pariaman, 2021)
This research is motivated by the fact that occurs in the field that the low ability of teachers in making instructional media that can influence the quality of schools. Varied and innovative learning media aims to create learning conditions that enable students to learn actively and be fun so that they can achieve optimal learning and achievement. The purpose of this study is to (1) measure the ability of teachers in making learning media with video application based on MsPowerpoint on Economics subjects through workshops, (2) knowing the picture the ability of teachers in making learning media with video-based applications Ms. Powerpoint in the subjects of the City of Padang City Madrasah Aliyah Economics through workshop activities. This type of research is descriptive, with a population of 25 people. Data collection techniques in this study used the experimental method. The results showed that with the implementation of media-making workshops, the ability of teachers to create and use video learning media based on Ms. Powerpoint applications can be improved.